An Integrated Procedure for Shape Optimization Applied to Fluid Flow - Steffens, L.M.; Alves, M.K. (Trends in Computational and Applied Mathematics, 2006)
This work proposes an integrated numerical procedure for the shape optimization of fluid flow problems. The procedure is named integrated since it combines various distinct modules for the solution to the problem, such as: geometric modeling, mesh generation for finite elements, nonlinear analysis of the fluid flow, sensitivity analysis, mathematical programming and shape optimization. The problem consists in the optimization of the contour shapes, aiming the reduction of the viscous dissipation produced by the flow around a given body or channel.